Gender Diverse Boardrooms and Earnings Manipulation: Does Democracy Matter? - Evangelos G. Varouchas; Stavros E. Arvanitis; Christos Floros (Risks)
We investigate the influence of boardroom gender diversity on earnings management. Drawing on a sample of European firms over the 2010–2023 period, we document an inverted U-shaped nexus between boardroom gender heterogeneity and earnings manipulation. Moreover, we also find that the Democracy Index moderates the curvilinear nexus by flattening the inverted U-curve and shifting the inflection point leftward. Our findings are consistent across various measures of earnings management and different econometric approaches, offering valuable insights for European policymakers.